MYTH OF REJECTING MARRIAGE PROPOSALS IN MADURA: A HERMENEUTICAL PERSPECTIVE IN ISLAMIC EDUCATION - Siti Nurjana; Qoniah Nur Wijayani (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
This research is based on the unique phenomenon of the myth of rejecting marriage proposals in Madura, which reflects the complex dynamics between Islamic values and local culture. This study aims to explore the meaning and interpretation of the myth and understand the relationship between Islamic education and local culture in the context of rejecting marriage proposals. The research method is qualitative and hermeneutic perspective with an in-depth interview approach with religious and community leaders, document studies to analyze local literature, and participatory observation to gain a direct understanding of social and cultural norms. The results showed that the hereditary belief of the ancestors, believed by her descendants, was that if a girl rejected her first proposal, she was believed to be exposed to reinforcements, which meant that she would have difficulty in finding a mate. This is influenced by the social dynamics, culture, and religious values of Islam. These findings reveal thematic patterns that illustrate the complex interplay between religious values and local traditions, providing a deeper understanding of the norms that shape of rejecting marriage proposals rejection in Madura. Islamic education plays a crucial role in shaping the moral and ethical foundations that influence decisions regarding marriage. The integration of local religious and cultural values in Madura is also seen through myths and hereditary beliefs regarding the rejection of proposals.